Differential Effects of Awake Glioma Surgery in “Critical” Language Areas on Cognition: 4 Case Studies - Djaina Satoer; Elke De Witte; Marion Smits; Roelien Bastiaanse; Arnaud Vincent; Peter Mariën; Evy Visch-Brink (Case Reports in Neurological Medicine)
Awake surgery with electrocorticosubcortical stimulation is the golden standard treatment for gliomas in eloquent areas. Preoperatively, mostly mild cognitive disturbances are observed with postoperative deterioration. We describe pre- and postoperative profiles of 4 patients (P1–P4) with gliomas in “critical” language areas (“Broca,” “Wernicke,” and the arcuate fasciculus) undergoing awake surgery to get insight into the underlying mechanism of neuroplasticity. Neuropsychological examination was carried out preoperatively (at T1) and postoperatively (at T2, T3). At T1, cognition of P1 was intact and remained stable. P2 had impairments in all cognitive domains at T1 with further deterioration at T2 and T3. At T1, P3 had impairments in memory and executive functions followed by stable recovery. P4 was intact at T1, followed by a decline in a language test at T2 and recovery at T3. Intraoperatively, in all patients language positive sites were identified. Patients with gliomas in “critical” language areas do not necessarily present cognitive disturbances. Surgery can either improve or deteriorate (existing) cognitive impairments. Several factors may underlie the plastic potential of the brain, for example, corticosubcortical networks and tumor histopathology. Our findings illustrate the complexity of the underlying mechanism of neural plasticity and provide further support for a “hodotopical” viewpoint.